Efektivitas Penerimaan E- Samsat Sumut Bermartabat Sebagai Media Pembayaran Pajak Kendaraan Bermotor (PKB) Pasca Pandemi Covid-19 - Murinanda Amalya Parinduri; Nurbaiti Nurbaiti; Laylan Syafina (Journal Economic Excellence Ibnu Sina, 2023)
This study aims to determine the effectiveness of E-Samsat Sumut Bermartabat as a medium of payment of Motor Vehicle Tax. The analysis method used is Descriptive Qualitative analysis using the Effectiveness formula. The data used are primary data and secondary data. The primary data was collected through interviews with two BPPRDSU employees as informants. For secondary data in this study in the form of documents, such as the Motor Vehicle Tax Revenue Report per year of BPPRDSU and Revenue per unit of E-Samsat BPPRDSU. The results of this study indicate that the presence of E-Samsat Sumut Bermartabat Post Covid-19 Pandemic which is where after the Covid-19 pandemic the interest in digital tran n / digital witnesses of the community has increased it can be seen from the increase in the use of E-Samsat Sumut Bermartabat as a medium for paying Motor Vehicle Tax, there is a difference in the level of Effectiveness from 2021 and 2022 which shows the level of Effectiveness in 2022 is higher than in the previous year, namely 2021 with a difference of 3.48%. This shows an increase even though it is still relatively not too big.